Legal Response to the Decision of the Business Competition Supervisory Commission Through Additional Examination Based on Supreme Court Regulation Number 3 of 2021 - Santosa, Palest Agista (Activa Yuris: Jurnal Hukum, 2025)
This study aims to find out about legal efforts to object to KPPU decisions through additional examinations based on Supreme Court Regulation Number 3 of 2021. The problem discussed in this study is the violation of the principle of justice in legal efforts to object to KPPU decisions that occur in the District Court. The data analysis method used in this study is the normative legal analysis method and comparative law. The normative legal method is used to analyze data that refers to legal norms contained in laws and regulations. The results of the data analysis in this study indicate a violation of the principle of justice in legal efforts to object to KPPU decisions. In practice, the burden of proof is carried out in an unbalanced manner, where the applicant cannot provide new evidence while the KPPU can strengthen and clarify the evidence through additional examinations ordered by the judge if the judge feels it is unclear. As a result, the objection applicant cannot strengthen his defense because he cannot add new evidence that can relieve the applicant